Nota sulle costruzioni a participio “pleonastico” nel greco biblico: il tipo ἐλθὼν κατῴκησεν (Atti del Sodalizio Glottologico Milanese, 2021)
Remarks on Biblical Greek pleonastic participles: the type ἐλθὼν κατῴκησεν. This paper deals with constructions such as ἐλθὼν κατῴκησεν, in which the participle form of a motion verb is juxtaposed to a finite verb and behaves as its aspectual modifier. It is in some sense pleonastic. These constructions frequently occur in the New Testament and the Septuagint, while they are rare in Classical Greek. The frequent occurrence of pleonastic participles in Biblical Greek can be explained as a case of (direct or indirect) interference with Hebrew pseudo-coordinate structures.
Keywords: Ancient Greek; New Testament; Septuagint; pleonastic participles; pseudo-coordination